Antioxidant Activity and Suppression of Intracellular Radical Generation of Streptomyces Strains and Genome Analysis of Strain ET3-23 - Khaing Zar Wai; Nantiya Bunbamrung; Pattama Pittayakhajonwut; Nisachon Tedsree; Somboon Tanasupawat; Rataya Luechapudiporn (Environment and Natural Resources Journal)
Actinomycetes, predominantly found in soil, represent a remarkable source of natural products. The natural antioxidants obtained from them have been employed for human infectious diseases. In particular, Streptomyces strains serve as significant sources of natural antioxidants with demonstrated health benefits. The in vitro antioxidant activity and the inhibition of intracellular radical generation by crude extracts from various Streptomyces strains were evaluated and the genome sequence of selected strains was analyzed. Strains CT2-10, NE1-12, and ET3-23 showed 16S rRNA gene sequence similarity to Streptomyces capoamus JCM 4734T (98.94%), Streptomyces nigra 452T (99.78%), and Streptomyces morookaense LMG 20074T (99.49%), respectively. The genome analysis of strain ET3-23 had 106 contigs, with a total length of 8121874 bp and an average G+C content of 71.46%. Ethyl acetate extracts of strains CT2-10, ET3-23, and NE1-12 exhibited, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity with IC50 555.9 µg/mL, 66.5 µg/mL, and 463.3 µg/mL and showed NO scavenging activity, except for CT2-10. Strain NE1-12 significantly inhibited ROS production induced by hydrogen peroxide on macrophage cells, while strains NE1-12 and CT2-10 inhibited NO production induced by lipopolysaccharides with IC50 82.4 µg/mL and 2.3 µg/mL, respectively. These findings suggest their ability to modulate NO production which is crucial in inflammatory responses and tissue injury. The antioxidant activities of Streptomyces strains indicate their potential as valuable sources of bioactive natural products and effective antioxidant agents, warranting further investigation for therapeutic applications.